Nexus of Workplace Spirituality, Employee Wellbeing, and Employee Commitment: A Comparison Between Social Enterprises and Other Organisations in Vietnam - Nguyen, Minh Hieu Thi (Journal of management, spirituality & religion, 2024)
This article examines the influence of workplace spirituality on employee wellbeing and employee commitment when financial needs are met with a focus on social enterprise. A survey of N = 595 Vietnamese employees and managers in both social enterprises (N = 138) and non-social enterprises (N = 457) indicated a (1) positive relationship between spirituality at work and wellbeing (adjusted R square = .521, pvalue<.001); (2) this relationship was moderated by the type of organisation, which is more positive for social enterprises adjusted R square = .527, pvalue<.001); and (3) a positive effect of types of organisation and workplace spirituality on the likelihood of committing to current employment. The study also found a higher level of workplace spirituality, employee wellbeing, and employee commitment in social enterprises. In short, the study is evidence for organisations and governments to foster wellbeing and promote social enterprises.